A New Species of Albizia from India - Sarni, K. C.; Naithani, H. B. (Indian Forester, 1979)
A new species of Albizia Durazz; A aranachalnuis Sahni et Naitbani from Arunachal Pradesh ili described Allied to A. mollis Boiv., it differs in having leaflets with truncate base, parallel to the secondary rhachis, faint secondary veins and pods up to 20 seeded. Seeds oblong and smaller.